Genomic Medicine in Nursing Education: A Study of Genetic Literacy, Attitudes, and Perspectives among Undergraduate Nursing Students - Norah M. Alyahya (Asian Journal of Pharmaceutics (AJP), 2025)
Background and Aim: Pharmacogenomics is an emerging discipline in molecular genetics with significant potential to influence treatment and health outcomes. Therefore, this study aimed to evaluate the genetic literacy, attitudes, opinions, and perspectives of nursing students regarding genomic medicine. Methods: A crosssectional design, utilizing an online questionnaire to collect data from nursing students enrolled in a university in the Riyadh region of Saudi Arabia. It was carried out over 4 months in 2025. The final questionnaire consisted of four sections: (1) Demographic information, (2) Knowledge of pharmacogenomics, (3) Attitudes toward genomics, and (4) Accessibility and availability of genetic testing. The collected data were analyzed using IBM the Statistical Package for the Social Sciences Version 26. Results: A total of 546 nursing students participated, with 45.8% males and 68.9% between 20 and 25 years old. The students demonstrated a good understanding of pharmacogenomics, with 60.8% correctly defining the term and 78% recognizing the role of genetic changes in adverse reactions. Notably, 93% understood that genetic modifications can impact drug efficacy. A substantial majority showed positive attitudes toward genetic testing, with 96.2% considering it for cancer treatment with fewer side effects and 87.4% for treatment with minimal adverse effects in the case of a family history of diabetes. Conclusion: Nursing students have a good understanding of pharmacogenomics, but knowledge gaps exist, particularly in basic genetics. Interest in genetic research and bio banking is low. The findings also highlight concerns about genetic testing accessibility and awareness of genetic discrimination protections. Targeted education and training are needed to address knowledge gaps and promote informed decision-making in genomic medicine.